Can innovative ambulance transport avert pregnancy-related deaths? One-year operational assessment in Ethiopia - Hagos Godefay; John Kinsman; Kesetebirhan Admasu; Peter Byass (Edinburgh University Global Health Society, 2016)
To maximise the potential benefits of maternity care services, pregnant women need to be able to physically get to health facilities in a timely manner. In most of sub-Saharan Africa, transport represents a major practical barrier. Here we evaluate the extent to which an innovative national ambulance service in Ethiopia, together with mobile phones, may have been successful in averting pregnancy-related deaths.